Integrating Christian values into educational curriculum: Developing students’ character in the digital era - Sitepu, Elisabeth; Munthe, Sharon Salsalina G. (Indonesian Research Journal in Education |IRJE|, 2025)
This study explores the integration of Christian values ​​in the education curriculum and its influence on the formation of students' character in the digital era. Using a qualitative approach and case study design, data were collected through semi-structured interviews, participant observation, and analysis of curriculum documents in several Christian schools. The study results indicate that Christian values, such as love, honesty, responsibility, and respect for others, were successfully instilled through creative and contextual learning methods. Students better understood the importance of implementing these values ​​in everyday life, both at school and outside. However, this study also identified challenges, such as the negative influences of the digital era, including gadget addiction and exposure to inappropriate content. This study concludes that integrating Christian values ​​into the education curriculum can effectively form students' character in the digital era. Education that integrates Christian values ​​aims to achieve academic excellence and to form students with strong character and integrity, ready to face the challenges of the times.